Hirschsprungova bolezen in kirurško zdravljenje - Pintar, Tadeja (Zdravniški vestnik, 2009)
Background Of patients with HD, 75-80% have rectosigmoid aganglionosis. Methods The basic principle in all surgical procedures is to bring the ganglionic bowel down to the anus. A one-stage pull-through operation (De la Torre-Mondragon) can be successfully performed in these patients using a transanal endorectal approach without opening the abdomen. Results and This procedure is associated with excellent clinical results and permits early postoperative conclusions feeding, early hospital discharge and no visible scars. The vast majority of patients treated with any one of the standard pull-through procedures achieve satisfactory continence and function with time. The attainment of normal continence is dependent on the intensity of bowel training, social background and respective intelligence of patients.
Keywords: Diagnosis; Hirschsprung Disease; Hirschsprungova bolezen; kirurško zdravljenje; Surgery